2006
DOI: 10.1108/01435120610715527
|View full text |Cite
|
Sign up to set email alerts
|

LIS professionals and knowledge management: some recent perspectives

Abstract: Purpose -To identify the general perspectives of library and information science professionals on knowledge management and examine their assessments of its potential values, benefits, opportunities and threats to the profession. Design/methodology/approach -An international survey was conducted using a web-based questionnaire. The questionnaire targeted LIS professionals around the world, through the use of the IFLA-L, KMDG-L mailing lists. Findings -The survey found an increased awareness among LIS profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 17 publications
1
24
0
2
Order By: Relevance
“…Knowledge management refers to the creation and subsequent management of an environment that encourages knowledge to be created, shared, learned and organized for the benefit of the firm (Sarrafzadeh et al 2006). The earliest research studies on knowledge management have been predominantly driven by technical perspective (i.e., information systems -IS).…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Knowledge management refers to the creation and subsequent management of an environment that encourages knowledge to be created, shared, learned and organized for the benefit of the firm (Sarrafzadeh et al 2006). The earliest research studies on knowledge management have been predominantly driven by technical perspective (i.e., information systems -IS).…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Knowledge management refers to the creation and subsequent management of an environment that encourages knowledge to be created, shared, learned and organized for the benefit of the firm (Sarrafzadeh et al, 2006). The earliest research studies on knowledge management have been predominantly driven by technical perspective (i.e., information systems -IS) (Hansen et al, 1999;Tuomi, 2002).…”
Section: Knowledge Management: Conceptual Foundationsmentioning
confidence: 99%
“…Koenig (2006) mentions that KM seems to be permanent, describing KM as a domain of stable mature growth with no indication of decline of publication volume, a very different profile in comparison to other business fads. KM has a future in LIS, and its durability has been confirmed in the studies conducted by Ajiferuke (2003), and Sarrafzadeh, Martin and Hazeri (2006). Davenport and Cronin (2000) describe KM in the LIS context as 'information management' (management of internal and external publications) by another name.…”
Section: Lis's Perceptions Of Kmmentioning
confidence: 85%
“…Within this context, several studies identified the market opportunities for information professionals (Moore, 1987;Apostle & Raymond, 1991). Similarly a number of authors describe that KM offers new career options and new job opportunities for graduates (Morris, 2001;Rehman & Chaudhry, 2005;Sarrafzadeh, Martin & Hazeri, 2006). Responding to the needs of current and future employers for information and knowledge professionals in the fast moving and exciting area of KM, LIS schools have adopted KM education.…”
Section: Emerging Employment Marketmentioning
confidence: 99%